A qualitative study of heterosexual men's attitudes toward and practices of receiving anal stimulation. Issue 6 (2nd June 2020) - Wignall, Liam; Scoats, Ryan; Anderson, Eric; Morales, Luis
Abstract: This study examines the practice of and attitudes toward anal sexual stimulation among 30 heterosexual undergraduate men attending a UK university. While scientific and popular belief throughout the twentieth century has considered anal pleasure to be only for gay or gender non-conforming men, we find participants discuss such pleasure openly, and some have explored physically receiving anal pleasure. Participants did not stigmatise sexual pleasure derived from anal play, challenging cultural narratives that conflate anal receptivity with being gay. We document how ignorance around the best practices for anal sex may impede pleasure and the further exploration of sexual pleasure and highlight areas where sexual health and education interventions may be beneficial.